2017
DOI: 10.1142/s1682648516500013
|View full text |Cite
|
Sign up to set email alerts
|

SURVEY OF ARIEMERELLA ANATIPESTIFEROUTBREAK IN SOUTHERN TAIWAN DUCK FARMS

Abstract: A septicemic outbreak in southern Taiwan duck farms in 2014 resulted in high mortality of ducklings. Samples from oral or cloacal sites of a®ected Muscovy and Pekin ducks were collected and the identity of the¯eld isolates was con¯rmed using Riemerella anatipestifer (RA) 16S rRNA and outer membrane protein A (OmpA)-speci¯c primers in polymerase chain reactions (PCR), with 15 isolates found positive for both 16S rRNA and OmpA. Detection of both the 16S rRNA and OmpA genes could be a rapid PCR test for RA. Serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In a previous study, it was showed that the overall morbidity and mortality of duck may vary and upto 75% mortality were recorded depending on the age and level of stress factors (Subramaniam et al, 2000;Crasta et al, 2002). The mortality rate in ducklings below 8 weeks of age was found to be higher than adult ducks (Yu et al, 2008, Phonvisay et al, 2017. Various factors predispose susceptible ducklings to the disease such as concurrent disease, adverse climate conditions and nutritional status (Vandamme et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, it was showed that the overall morbidity and mortality of duck may vary and upto 75% mortality were recorded depending on the age and level of stress factors (Subramaniam et al, 2000;Crasta et al, 2002). The mortality rate in ducklings below 8 weeks of age was found to be higher than adult ducks (Yu et al, 2008, Phonvisay et al, 2017. Various factors predispose susceptible ducklings to the disease such as concurrent disease, adverse climate conditions and nutritional status (Vandamme et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Poor sanitation, nutrient deficiency, adverse ( e.g . stressful) environments or climates, and concomitant diseases usually predispose fowl to outbreaks of R. anatipestifer infection, especially those under 8 weeks old (3, 26, 34). In a survey of samples of waterfowl in Taiwan between 2006 and 2007, the significant prevalence (84.4%) of R. anatipestifer in farms revealed the potential risk of an outbreak (4, 14).…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of nonserotypable R. anatipestifer strains was also found in the survey conducted in Southern Taiwan duck farms. Among 11 tested strains, 6 of them were nonserotypable, accounting for 54.54% ( Phonvisay et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%